ACCELERATING THE 2025 SUSTAINABLE DEVELOPMENT GOALS (SDGS): THE ROLE OF INVESTMENT AND EDUCATIONAL ENVIRONMENTS IN ADDRESSING ECONOMIC RECESSION ISSUES - Radeswandri; Mery Berlian; Herlinda (Jurnal Dinamika Ekonomi Syariah, 2026)
This research has two main aspects: an analysis of human resource (HR) readiness in the context of accelerating the 2025 Sustainable Development Goals (SDGs), particularly in relation to the economic recession, and a mapping of the number of human resource students at Universitas Terbuka (UT) to support the SDGs. In analyzing human resource readiness related to the 2025 SDGs and the economic recession, we identified several important factors. First, the majority of respondents had varying understandings of HR in a recessionary situation, with an awareness of the crucial role of HR in overcoming the recession and achieving the SDGs. Second, respondents acknowledged the importance of investing in HR development in facing the recession. Third, prior knowledge of HR development related to the SDGs varied, indicating potential for improved understanding. Fourth, access to technology that supports HR understanding has significant limitations. Fifth, interest in developing HR in the context of the economic recession is quite high. The results of the mapping of UT's student HR reveal other important things. UT has a significant number of students with diverse educational backgrounds and skills, which can be a great potential in supporting various SDG targets. However, efforts are needed to increase student awareness and understanding of the SDGs and their contributions. Furthermore, this mapping identified specific skills development needs relevant to the SDGs, such as leadership and technology skills. To maximize the contribution of UT students in supporting the SDGs, we recommend a series of actions. First, UT should integrate SDG concepts into the curriculum and conduct regular awareness campaigns. Second, UT should evaluate and update the curriculum to include skills training relevant to the SDGs. Third, UT should establish partnerships with SDG-related organizations and provide students with practical experience through SDG-related projects. Fourth, UT should expand career development resources and provide information on job opportunities that support sustainable development. Fifth, UT should encourage student innovation and research in sustainable economic solutions. Finally, UT can organize mentoring and guidance programs by experienced professionals. By implementing these recommendations, UT can harness the potential of its students as powerful agents of change in supporting the SDGs, especially in the face of the challenges of economic recession, and play a crucial role in achieving these sustainable development goals